Sex-Specific Bands in Dioecious Plant Jernang Rattan (Daemonorops draco) Based on RAPD Markers - Amanda Nurhafitri; Mansyurdin Mansyurdin; Djong Hon Tjong; Syamsuardi Syamsuardi; Revis Asra; Muhammad Idris (Universitas Labuhanbatu, 2026)
Background: Daemonorops draco (Willd.) Blume, or dragon’s blood rattan, is a dioecious species that produces high-value resin but is increasingly threatened by habitat degradation. Effective cultivation and conservation require early identification of male and female plants, which remains challenging at the seedling stage. Although RAPD markers have been used for sex identification in dioecious plants, studies on D. draco are still limited. Therefore, this study aims to screen sex-specific bands in D. draco using the RAPD approach. Methodology: Samples of six male and six female individuals collected from Jambi were analyzed, with DNA isolated using a modified CTAB protocol and amplified using 44 RAPD primers. The products were separated by 2% agarose gel electrophoresis. Bands were considered sex-specific if they consistently appeared only in one sex and were absent in the other. Findings: Out of the 44 primers tested, 39 successfully amplified D. draco DNA, generating a total of 662 bands. Among them, primer OPA-14 (455 bp) and OPC-19 (310 bp) produced male-specific bands that were consistently present in all male individuals, while primer OPB-10 (850 bp) generated a female-specific band detected in all female individuals. The male-specific 455 bp band from OPA-14 and 310 bp from OPC-19, and the female-specific 850 bp band from OPB-10 were identified. These bands are recommended for development into SCAR markers for early sex identification in D. draco. Contributions: The findings support the provision of male and female seedlings to enhance conservation and cultivation programs